#Stayhome: Language in tourism advertisements on Instagram: English dominates in online tourism ads from multilingual societies, but local languages are used to create local authentic effect. Issue 1 (March 2023) - Wilson, Guyanne; Zappe, Esther; Silbermann–Schön, Jonas; Guilliaume, Kai; Altwicker, Rebecca; Tapari, Mariana; Wolf, Marina; Benitez Torrejon, Mercedes; Mamadaliyeva, Mushtariy; Busskamp Castro, Anna Lucia
Abstract : In Fiji, Ghana, Jamaica, and the Maldives, the tourism sector is an important source of economic wealth. For example, in the Maldives tourism accounts for around a quarter of total GDP and is a main source of employment (Meierkord, 2018: 5). Similarly, the role of tourism as one of Jamaica's main industries has been stated in Deuber (2014: 29), and Hundt, Zipp and Huber (2015: 691) also mention that tourism is one of the key industries and employment sectors in Fiji. While many of these destinations use traditional channels of advertising such as print magazines, a considerable amount of advertising is carried out online via social media.